Using group ratings to assess household food security: empirical evidence from southern Africa - Carletto, Calogero; Masangano, Charles; Bergeron, Gilles; Morris, Saul Sutkover (Informa UK Limited, 2001)
This article addresses the reliability and validity of household welfare rankings using the Group Ratings (GR) method. The GR aimed to measure the food security status of 142 households in seven villages in Malawi. Sets of informant groups rated households from their own community. Results show that the reliability of the method was no more than fair to moderate, and was particularly low for households falling in the middle category of 'intermittently food insecure'. Consensus ratings from the GR sessions were then compared with a number of alternative indicators of food security from a quantitative household survey. GR were associated with the more visible aspects of food security, such as household asset and livestock holdings, but associations with less visible aspects of food security were weaker. The strength of these associations varied from village to village.